Anti-doping education for coaches: Qualitative insights from national and international sporting and anti-doping organisations - Patterson, L. B.; Backhouse, S. H.; Duffy, P. J. (Sport Management Review, 2016)
Within anti-doping efforts, an emphasis has been placed on the importance of providing education programmes to key stakeholder groups, including coaches. Yet, very little is known about current coach education provision in the anti-doping domain across countries and sports. Therefore, this study aimed to: (1) establish the current status of anti-doping education for coaches; (2) gain an understanding of the system through which anti-doping education is provided to coaches; and, (3) explore the opportunities for future education provision. This was done through semi-structured interviews with thirteen individuals responsible for managing anti-doping education within national and international sporting and anti-doping organisations. Most stakeholders acknowledged the importance of providing education programmes for coaches. Some already had provision in place and others were in the process of developing programmes. However, the current focus is on sportspeople and the degree to which sporting and anti-doping organisations are able to devise, implement and evaluate anti-doping education programmes for coaches is hindered by the contextual constraints they face. These include a lack of resources and limited interagency coordination, as well as challenges to overcome negative perceptions of `anti-doping` efforts. Taken together, the findings indicate that policy expectations regarding anti-doping education for coaches are not being fully operationalised, and this situation is unlikely to change without: (1) greater direction and regulation of the system through which education is provided; (2) frequent and effective communication and cooperation between Code signatories; and, (3) increased fiscal and human capital investment at every level of the sporting hierarchy. Ultimately, until anti-doping education is shown to be a key priority for decision makers within sporting organisations (i.e., chief executives and board members), it is unlikely to become a central priority for coaches).